Identifying Conservation Priority Sites for Saraca Asoca: An Important Medicinal Plant Using Ecological Niche Models - Sumangala, R. C.; Rosario, Sachin; Charles, Bipin; Ganesh, D.; Ravikanth, G. (Indian Forester, 2017)
Saraca asoca (Roxb.) de Wilde belonging to family Caesalpiniaceae has been used to manage gynecological disorders and infections besides being used for treating bacterial infections, skin problems, worm infestations, cardiac and circulatory problems. Almost all parts of the plant are considered therapeutically valuable. The plant has been extensively mentioned in several folklores besides ayurvedic literature. This has lead to the availability of several commercial S. asoca formulations recommended for different ailments. Owing to a large number of herbal formulations, the domestic demand for Ashoka bark in India was reported to be more than 15,000 metric tonnes. This increased demand has led to extensive and indiscriminate extraction of S. asoca resources in several parts of country. In this paper, using distribution records of S. asoca in India, the hotspots of distribution of S. asoca have been identified using Ecological Niche Modelling (ENM) tools. ENMs use species occurrence records along with climatic and other environmental variables to generate species distribution maps. These distribution maps are used to identify suitable habitats for cultivation of species to meet the demand of herbal industry. The distribution of S. asoca for future climate scenarios has also been modelled. Predicting how species distribution will change in the wake of future global climate change, is important to develop effective conservation strategies.